(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2024)
Workers spend most of their time in a work environment, making job satisfaction crucial for them. At PT Kereta Api Indonesia UPT Balai Yasa Yogyakarta, job satisfaction not only impacts individual employees but also the quality of transportation services provided. Strong coworker support and high levels of work motivation are frequent factors influencing job satisfaction. Work motivation, in this context, serves as a link that explains how support from coworkers affects job satisfaction. People who experience support from their coworkers feel more competent at work, which boosts motivation. Individuals who are motivated to achieve goals feel better satisfaction in their work. This study aims to determine the impact of coworker support on job satisfaction mediated by work motivation at PT Kereta Api Indonesia UPT Balai Yasa Yogyakarta. 50 respondents, including both permanent and temporary employees, provided the data for this study. The research is quantitative, and data analysis is done using SMARTPLS. The results showed that coworker support has no direct effect on job satisfaction but has a significant indirect effect through motivation. The findings highlight the importance of leaders being able to strengthen supportive relationships among workers to stimulate work motivation and increase satisfaction in the workplace.